Sixth Form Pathways Programme for 7 Years of Secondary Education in Jamaica: Version 1 - Jamaica. Ministry of Education, Youth & Information (MoEYI) (Ministry of Education, Youth and Information, Jamaica, 2021)
The MoEYI has been implementing what is referred to as the K - 13 Strategy in an effort to ensure that all Jamaican learners have access to education from the early childhood to secondary levels of the education system. The Ministry is committed to addressing the current challenge whereby only 35% of the average 40,000 Grade 11 students transition to a sixth form programme. To this end, the Career Advancement Programme and the programmes offered by the Centre of Occupational Studies (COS) have been integrated into the current sixth form programme to form the Sixth Form Pathways Programme (SFPP). Under the framework, provision is being made for every student aged 16 to 18 years, having completed Grade 11 (i.e. at least five years of secondary education), to access an additional two years of placement in the education system to pursue Grades 12 and 13. Initially, students will be able to access their programme either at the school they attended or at a tertiary institution through partnerships which have been established with Community Colleges, Teachers Colleges, and Universities (public and private)
Keywords: sixth form; pathways programme; secondary education; Jamaica